Perbandingan Kinerja Keuangan Bank Perkreditan Rakyat (BPR) Sebelum dan Sesudah Penerapan Tata Kelola (Good Gorporate Governance) Di Provinsi Jambi - Adi Surahmat; Mukhzarudfa; Yudi (Magister Ilmu Akuntansi Universitas Jambi, 2020)
The purpose of this study is to look at financial performance and explain the financial performance comparison of Rural Credit Banks in Jambi Province before and after the implementation of governance and determine compliance with the implementation of governance provisions by Rural Credit Banks in Jambi Province, as measured through the Earning Assets Quality Ratio (KAP) Net Non Performing Loans (NPLs) Ratio, Return on Assets (ROA) Ratio, Operating Cost Ratio (BOPO), Loan To Deposit Ratio (LDR) and Cash Ratio (CR). This research is a quantitative descriptive study with data sourced from Bank Perkreditan Rakyat publication reports. Hypothesis testing will use descriptive statistics, Normality Test and Paired Sample T-test. In addition, the researcher also conducted a survey to the Rural Bank to see the level of compliance with governance provisions. The results showed that the financial performance of 15 Rural Credit Banks before and after the implementation of governance was considered insignificant and the results of the different tests used Paired Sample T-test to KAP Ratio, Net NPL Ratio, ROA Ratio, BOPO Ratio, LDR and Cash Ratio to all The Rural Credit Bank in Jambi Province shows no difference in financial performance. However, the survey results show an increase in compliance of the Rural Credit Bank in meeting the conditions required by the OJK in accordance with the specified deadline.